1993
DOI: 10.1159/000284795
|View full text |Cite
|
Sign up to set email alerts
|

On Perception of Complex Sound in Schizophrenia and Mania

Abstract: Eleven schizophrenic psychotic and 11 manic psychotic patients have been compared with each other and with a reference group of 34 dentists with respect to their emotional experience of seven complex nonverbal sounds. A rating form was used which measures three factors of emotional perception: tension – relaxation (factor I), gaiety – gloom (factor II), and attraction – repulsion (factor III). Analyses of variance of the factor scores revealed main tendencies between the psychopathological groups in factor I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Irrespective of symptomatology, outpatients reported a greater attraction towards digitally-manipulated Bach compositions than controls, despite having an otherwise 'correct' experience of their valence and arousal. An earlier series of studies with over 100 psychiatric patients observed a similar effect (Nielzén & Cesarec, 1982;Nielzén, Olsson, & Ohman, 1993): patients undergoing psychosis were more attracted to music, and the difference was especially pronounced when negatively-valenced stimuli were at play. In one study (Nielzén & Cesarec, 1982), patients were drawn to those short pieces of orchestral music which controls had found the least appealing.…”
Section: Studymentioning
confidence: 78%
See 3 more Smart Citations
“…Irrespective of symptomatology, outpatients reported a greater attraction towards digitally-manipulated Bach compositions than controls, despite having an otherwise 'correct' experience of their valence and arousal. An earlier series of studies with over 100 psychiatric patients observed a similar effect (Nielzén & Cesarec, 1982;Nielzén, Olsson, & Ohman, 1993): patients undergoing psychosis were more attracted to music, and the difference was especially pronounced when negatively-valenced stimuli were at play. In one study (Nielzén & Cesarec, 1982), patients were drawn to those short pieces of orchestral music which controls had found the least appealing.…”
Section: Studymentioning
confidence: 78%
“…Review of musical experiences in schizophrenia uncovered consistent evidence of overarousal. Varied patient samples had highly arousing experiences, as indexed by miscellaneous measures: stabilized patients as well as individuals undergoing psychosis or suffering from a steep cognitive decline reached higher than normal excitement, according to self-reported data (Nielzén & Cesarec, 1982; Nielzén et al, 1993), spectral EEG (Burge & Siebert, 2010; Günther et al, 1991; 1993), or imaging data (Dyck et al, 2014). Arousal typically rises in persons who are sensitized by the symptoms of psychosis or their connotations (Aleman & Kahn, 2005; Cohen & Minor, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research has mainly focused on normal subjects being musicians or non-musicians. An interesting study has been published on a patient with central auditory processing disorder [25], with documentation of increases in cerebral blood flow in the lateral prefrontal cortices, the middle temporal cortices and the cerebellar hemispheres as a consequence of attentive listening. This research in central auditory pathology is only recently developing as the complexity of the auditory cortex with its 15 known subdivisions is starting to be appreciated.…”
Section: Reviewmentioning
confidence: 99%